PROTEIN SYNTHESIS BY ISOLATED PEA NUCLEOLI - Birnstiel, Max L. (The Rockefeller University Press, 1963)
A new method is described for the preparation of active, nucleus-free nucleoli and chromatin in relatively high purity and in sufficient quantities to permit biochemical and electron microscopic investigation. This method consists of disintegrating previously isolated nuclei by grinding with glass beads in an isotonic medium thus liberating structurally intact nucleoli and chromatin threads. Nucleoli and chromatin are then purified by differential centrifugation in Ficoll solutions. A study of the chemical composition, submicroscopic structure, and biological activity of the nucleolar preparation has been made. An equivalent study of the chromatin material has also been carried out in order to assess the significance of chromosomal contamination in nucleolar protein synthesis. The isolated nucleoli rapidly incorporate leucine-C(14) into acid and base stable compounds in vitro. Such incorporation lasts for 20 minutes at 37°C and is enhanced by the addition of an energy-regenerating system and a complete amino acid mixture. It is independent of the nuclear Ph 5 enzymes. The bulk of the incorporated label is recovered in the residual, ribosome-like nucleolar protein fraction and a small percentage is found in the acid-extractable basic proteins. The rate of protein synthesis by isolated nucleoli is more rapid than that occurring in the chromatin fraction. This is taken as an additional proof that the nucleolus is the principal site of protein synthesis in the interphase pea nucleus.